Effect of Fermented Vegetable Waste Supplemented with Fish Flour Waste on Nutritional Quality and Performance of Broiler - Nuraliah, Siti; Palayukan, Jisril; Indah, Andi Sukma; Ikram, Ikram; Irsam, Irsam; Fikri, Zen; Herman, Herman (Jurnal Agripet, 2025)
This study aims to evaluate the effects of fermented vegetable waste supplemented with varying levels of fish waste flour on the nutritional composition of the feed and its impact on broiler performance. The experiment employed a Completely Randomized Design (CRD) with four treatments and four replications. The treatments were as follows: T0Vegetable Waste (VW) without Fish Waste Flour Supplementation (FWFS); T1VW+5%FWFS; T2VW+10%FWFS; and T3VW+15%FWFS. Parameters measured included proximate composition and broiler performance indicators. The results demonstrated that the fermentation of vegetable waste with fish waste flour at varying concentrations significantly affected (P0.05) moisture content, crude protein, crude fiber, ash content, feed intake, feed conversion ratio (FCR), and body weight. However, crude fat and nitrogen-free extract (NFE) contents were not significantly affected (P0.05). The supplementation of 10% fish waste flour (T2) yielded the highest values for crude protein, crude fat, and moisture, and also resulted in the best body weight gain and feed conversion ratio among the treatments. In conclusion, the inclusion of 10% fish waste flour in fermented vegetable waste is recommended, as it provides optimal nutritional quality and enhances broiler performance.